Korean War 1129 : 1950.6.25-1953.7.27 - Lee, Joong Keun (Seoul : Woojung Books, 2015)
Abridged translation of : 6.25 Chonjaeng 1129-il, published in 2013
Keywords: Korean war, 1950-1953.; Korean war -- Campaigns; Korean war -- Chronology